Diagnostik Coronavirus Disease 2019 (COVID-19) dengan Pemeriksaan Laboratorium Mikrobiologi Klinik - Damo, Natasya Y.; Porotu'o, John P.; Rambert, Glady I.; Rares, Fredine E. S. (Universitas Sam Ratulangi, 2021)
Abstract: The world is in fear of the pandemic Coronavirus Disease (COVID-19) which is so deadly, the World Health Organization (WHO) declared the world a global health emergency. The number of confirmed cases is still very high until now, even in Indonesia this pandemic is still not over. The transmission is so fast and wide, plus the current clinical manifestations of COVID-19 have varied, ranging from asymptomatic to severe. This literature review aims to determine the Diagnostic of COVID-19 with the most appropriate Clinical Microbiology Laboratory Examination and to find out the importance of Clinical Microbiology Laboratory examinations in COVID-19 Diagnostics. The method used is in the form of literature studies from several scientific sources that are accurate and valid regarding the Diagnostic of COVID-19 with Clinical Microbiology Laboratory Examination. The results showed that Polymerase Chain Reaction (PCR) is the gold standard in detecting COVID-19 although there are several factors that can affect the results of the PCR examination which then cause false negatives / positives. Conclusion Clinical Microbiology Laboratory Examination is very important and very helpful. Diagnostic COVID-19 in the Microbiology Laboratory can be done by using Rapid Diagnostic Test (RDT) Antigen, RDT Antibody, PCR, and Virus Culture. Diagnostic COVID-19 with the recommended Clinical Microbiology Laboratory Examination and the gold standard is PCR examination. However, there are also several factors that can affect the results of the PCR examination.Keywords: diagnostic, COVID-19, Clinical Microbiology LaboratoryÂ Â Abstrak: Dunia sedang dalam ketakutan dengan pandemi Coronavirus Disease (COVID-19) yang begitu mematikan, Organisasi Kesehatan Dunia (WHO) menyatakan dunia sebagai darurat kesehatan global. Jumlah kasus yang terkonfirmasi masih sangat tinggi hingga saat ini, bahkan di Indonesia pandemi ini masih belum berakhir. Penularannya begitu cepat dan luas, sertta manifestasi klinis COVID-19 yang bervariasi, mulai dari asimtomatik hingga parah. Tinjauan pustaka ini bertujuan untuk mengetahui Diagnostik COVID-19 dengan Pemeriksaan Laboratorium Mikrobiologi Klinik yang paling sesuai dan untuk mengetahui pentingnya pemeriksaan Laboratorium Mikrobiologi Klinik dalam Diagnostik COVID-19. Metode yang digunakan berupa studi pustaka dari beberapa sumber ilmiah yang akurat dan valid mengenai Diagnostik COVID-19 dengan Pemeriksaan Laboratorium Mikrobiologi Klinik. Hasil penelitian menunjukkan bahwa Polymerase Chain Reaction (PCR) merupakan gold standard dalam mendeteksi COVID-19 meskipun terdapat beberapa faktor yang dapat mempengaruhi hasil pemeriksaan PCR yang kemudian menimbulkan false negatif/positif. Kesimpulan Pemeriksaan Laboratorium Mikrobiologi Klinik sangat penting dan sangat membantu. Diagnostik COVID-19 di Laboratorium Mikrobiologi dapat dilakukan dengan menggunakan Antigen Rapid Diagnostic Test (RDT), Antibodi RDT, PCR, dan Kultur Virus. Diagnostik COVID-19 dengan Pemeriksaan Laboratorium Mikrobiologi Klinik yang direkomendasikan dan menjadi gold standard adalah PCR. Namun, ada juga beberapa faktor yang dapat mempengaruhi hasil pemeriksaan PCR.Kata Kunci: diagnostik, COVID-19, Laboratorium Mikrobiologi Klinik